Optimal design strategies for relative potency using the two-parameter log-logistic model - Pattaraporn Tusto (2018)
© 2016 - IOS Press and the authors. All rights reserved. In this paper, we focus on the D- and Ds-optimal designs for two-parameter log-logistic (LL2) relative potency model where the response variables are normal and binomial distributions. The D- and Ds-optimal designs are obtained by using D-optimal design and nesting strategy criterions, respectively. Furthermore, the general equivalence theorems is used to guarantee the D- and Ds-optimal designs. The results show that we obtain four support points for D-optimal designs and two support points for Ds-optimal designs.